The influence of nonuniform ambient noise on crustal tomography in Europe - Basini, P; Nissen-Meyer, T; Boschi, L; Casarotti, E; Verbeke, J; Schenk, O; Giardini, D (2013)
Ambient-noise seismology is of great relevance to high-resolution crustal imaging, thanks to the unprecedented dense data coverage it affords in regions of little seismicity. Under the assumption of uniformly distributed noise sources, it has been used to extract the Green's function between two receivers. We determine the imprint of this assumption by means of wave propagation and adjoint methods in realistic 3-D Earth models. In this context, we quantify the sensitivity of ambient-noise cross-correlations from central Europe with respect to noise-source locations and shear wave-speed structure. We use ambient noise recorded over 1 year at 196 stations, resulting in a database of 864 cross-correlations. Our mesh is built upon a combined crustal and 3-D tomographic model. We simulate synthetic ambient-noise cross-correlations in different frequency bands using a 3-D spectral-element method. Traveltime cross-correlation measurements in these different frequency bands define the misfit between synthetics and observations as a basis to compute sensitivity kernels using the adjoint method. We perform a comprehensive analysis varying geographic station and noise-source distributions around the European seas. The deterministic sensitivity analysis allows for estimating where the starting crustal model shows better accordance with our data set, and gain insight into the distribution of noise sources in the European region. This highlights the potential importance of considering localized noise distributions for tomographic imaging, and forms the basis of a tomographic inversion in which the distribution of noise sources may be treated as a free parameter similar to earthquake tomography. © 2013. American Geophysical Union. All Rights Reserved.